Patient perspectives on primary care for multimorbidity: An integrative review. (8th September 2022) - Moody, Elaine; Martin‐Misener, Ruth; Baxter, Larry; Boulos, Leah; Burge, Fred; Christian, Erin; Condran, Brian; MacKenzie, Adrian; Michael, Elizabeth; Packer, Tanya; Peacock, Kylie; Sampalli, Tara; et al.
Abstract: Introduction: Improving healthcare for people with multiple chronic or ongoing conditions is receiving increased attention, particularly due to the growing number of people experiencing multimorbidity (MM) and concerns about the sustainability of the healthcare system. Primary care has been promoted as an important resource for supporting people with MM to live well with their conditions and to prevent unnecessary use of health care services. However, traditional primary care has been criticized for not centring the needs and preferences of people with MM themselves. Our aim was to conduct a review that centred on the perspective of people with MM in multiple ways, including having patient partners co‐lead the design, conduct and reporting of findings, and focusing on literature that reported the perspective of people with MM, irrespective of it being experimental or nonexperimental. Methods: We searched for published literature in CINAHL with Full Text (EBSCOhost) and MEDLINE All (Ovid). Findings from experimental and nonexperimental studies were integrated into collaboration with patient partners. Results: Twenty‐nine articles were included in the review. Findings are described in five categories: (1) Care that is tailored to my unique situation; (2) meaningful inclusion in the team; (3) a healthcare team that is ready and able to address my complex needs; (4) supportive relationships and (5) access when and where I need it. Conclusion: This review supports a reorientation of primary care systems to better reflect the experiences and perspectives of people with MM. This can be accomplished by involving patient partners in the design and evaluation of primary care services and incentivizing collaboration among health and social supports and services for people with MM. Patient or Public Contribution: Patient partners were involved in the design and conduct of this review, and in the preparation of the manuscript. Their involvement is further elucidated in the manuscript text.